2010
DOI: 10.1074/jbc.m109.073387
|View full text |Cite
|
Sign up to set email alerts
|

PemK Toxin of Bacillus anthracis Is a Ribonuclease

Abstract: Bacillus anthracis genome harbors a toxin-antitoxin (TA) module encoding pemI (antitoxin) and pemK (toxin). This study describes the rPemK as a potent ribonuclease with a preference for pyrimidines (C/U), which is consistent with our previous study that demonstrated it as a translational attenuator. The in silico structural modeling of the PemK in conjunction with the site-directed mutagenesis confirmed the role of His-59 and Glu-78 as an acid-base couple in mediating the ribonuclease activity. The rPemK is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…For example, peptide inhibitors of the B. anthracis PemIK interaction were designed to mimic the C -terminal toxin-binding region of the antitoxin [193]. The toxin PemK cleaves single-stranded RNAs, and toxicity is inhibited by the antitoxin PemI.…”
Section: Exploitation Of Ta Systems For the Development Of Novel Amentioning
confidence: 99%
See 1 more Smart Citation
“…For example, peptide inhibitors of the B. anthracis PemIK interaction were designed to mimic the C -terminal toxin-binding region of the antitoxin [193]. The toxin PemK cleaves single-stranded RNAs, and toxicity is inhibited by the antitoxin PemI.…”
Section: Exploitation Of Ta Systems For the Development Of Novel Amentioning
confidence: 99%
“…Deletion mutant studies showed that the C -terminal fragment of PemI is responsible for PemK binding [194]. The two peptides (LLFQHLTE and RRGYIEMG) block the PemIK interaction and inhibit in vitro ribonuclease activity of the PemK toxin, whereas peptides derived from the N -terminal fragment of PemI do not influence the TA interaction [193]. A rationally designed octapeptide (SKIGAWAS) is predicted to form an α-helix and to occupy the TA binding interface [194].…”
Section: Exploitation Of Ta Systems For the Development Of Novel Amentioning
confidence: 99%
“…PemK, of the B. anthracis PemIK TA module, cleaves single-stranded RNAs and is inhibited by the binding of antitoxin PemI [64]. Analysis of PemI deletion variants indicated that the C-terminus is required to bind to PemK.…”
Section: Efforts Towards Discovering Toxin Activatorsmentioning
confidence: 99%
“…Analysis of PemI deletion variants indicated that the C-terminus is required to bind to PemK. Based on this information, six hepta- and octa-peptides, representing fragments of the antitoxin located in a predicted helical region within the TA binding interface, were analyzed for their ability to inhibit the PemI-PemK interaction [64]. ELISA results revealed that each designed peptide was capable of preventing the PemI-PemK interaction to a certain extent, whereas nonspecific 15- and 9-residue peptides based on the N-terminus of PemI did not affect the PemI-PemK interaction [64].…”
Section: Efforts Towards Discovering Toxin Activatorsmentioning
confidence: 99%
See 1 more Smart Citation